A comparative evaluation of antioxidant and antidiabetic potential of peel from young and matured potato. (1st March 2015) - Arun, K.B.; Chandran, Janu; Dhanya, R.; Krishna, Priya; Jayamurthy, P.; Nisha, P.
Abstract: In the present study antioxidant and antidiabetic potentials of potato peels at two different stages of maturity were evaluated and compared. Peels of young and mature potatoes (YP and MP) were sequentially extracted with hexane (HMP, HYP), ethyl acetate (EMP, EYP) and methanol (MMP, MYP). EMP and EYP were found to possess the highest phenolic content (83.2 and 44.14 mg GAE/g dry weight, respectively) and maximum radical scavenging efficacy for different antioxidant assays performed. EYP demonstrated better α-glucosidase inhibition activity (IC50 -197.13 µg), intracellular ROS scavenging and induce glucose uptake in L6 rat skeletal muscle cells. Phenolic profiling of compounds (gallic, caffeic, ferulic and chlorogenic acids) in the active extracts were established using HPLC. The study demonstrated that YP exhibited better bioactive potential than that of MP. YP could be an excellent source of bioactive phytochemicals with antioxidant and antidiabetic potential.